Heuristic Logic Resynthesis Algorithms at the Core of Peephole Optimization - Lee, Siang-Yun; Micheli, Giovanni De (IEEE transactions on computer-aided design of integrated circuits and systems, 2023)
Logic resynthesis is one of the core problems in modern peephole logic optimization algorithms. Given a target function and a set of existing functions, logic resynthesis asks for a circuit reusing some of the existing functions and generating the target. While exact methods such as enumeration and SATbased synthesis guarantee optimal solutions, limitations on the problem size are inevitable due to scalability concerns. In this work, we propose heuristic resynthesis algorithms for ANDbased, majority-based, and multiplexer-based circuits, which are scalable in all aspects. Used as the core of high-effort optimization, our heuristic resynthesis algorithms play a key role in enabling 2-3% further size reduction on benchmarks that are already processed by state-of-the-art optimization flows.